Adaptation of in vitro methodologies to estimate the intestinal digestion of lipids in ruminants - Vinyard, James R. (2021)
The objective of this study was to adapt existing in vitro methodologies to determine the extent of intestinal digestion of corn oil (CO), canola oil (CA), and beef tallow (BT) via manipulation of incubation length and concentrations of lipase, bile, and calcium within a buffer solution. Unless otherwise stated, 0.5 g of each lipid source were incubated separately and in triplicate, with triplicate batch culture runs for each treatment in 40 mL of 0.5 M KH2PO4 (pH = 7.6) for 24 h with pancreatin (8 g/L), bovine bile (2.5 g/L), and CaCl2 (10 mM). Individually, concentrations of pancreatin, bile, and CaCl2, as well as incubation length were tested. To examine the use of this assay to estimate in vitro total tract digestion, a KH2PO4 solution with concentrated amounts to reach the same final concentrations of pancreatin, bile, and Ca were used as the third step in a three-step total tract digestibility procedure. Free glycerol and free fatty acid (FFA) concentrations were measured using colorimetric assays as indicators of digestion. Data wereanalyzed as a completely randomized block design (block = run), using the Glimmix procedure of SAS. For each lipid source, free glycerol increased with increasing pancreatin; however, FFA was lowest at 0 g/L pancreatin but was similar at 6, 8, and 10 g/L. Both glycerol and FFA were greater for 2.5 and 5 g/L of bile than for 0 g/L for each lipid source. Calcium concentration did not affect glycerol or FFA for either CO or CA; however, glycerol and FFA for BT were greater when calcium was included at 5 and 10 mM than at 0 mM. For all fat sources, free glycerol and FFA increased after 1 h until 12 h, but did not increase from 12 to 24 h. When a concentrated mixture was used following fermentation and acidification steps, digestibility using FFA concentration increased as compared to just adding buffer; however, free glycerol concentration was indeterminable. Thus, free glycerol and FFA can be used as indicators of lipid digestion when a lipid source is incubated for at least 12 h in a buffer solution containing 8 g/L pancreatin, 2.5 g/L bile, and 5 mM Ca when only estimating in vitro intestinal digestion; however, when utilizing this assay in a three-step in vitro total tract digestibility procedure, only FFA can be used.